A blockchain-enabled 5G authentication scheme against DoS attacks. Issue 1 (February 2021) - Chow, Man Chun; Ma, Maode
Abstract: The 5G network is designed to accommodate the increasing number of connected devices with higher speed, lower latency, and better security. To improve the network security and robustness, the Third Generation Partnership Project (3GPP) has standardized the 5G-AKA protocol for mutually authenticating user equipment (UE), base stations, and the core network. However, since there will be more devices in the 5G network, the denial-of-service (DoS) attacks are much easier to be carried out than ever before. In this paper, we address the security issues in the 5G network by introducing the blockchain-enabled authentication and key agreement scheme for the 5G Networks. Our proposed scheme uses private blockchain to provide a distributed database to store all authentication records. Also, we exploit the trapdoor collision property of the chameleon hash function, such that the entries in the blockchain can verify the incoming authentication requests. Furthermore, a subscription concealed identifier (SUCI) is mandatory in our protocol to protect the anonymity of the devices, and ECDH is employed to generate a session key. We use Scyther Tool to verify our protocol formally, and the security analysis shows that our protocol can achieve perfect forward secrecy, device anonymity, and mutual authentication and key agreement. Our scheme is also resistant to replay attacks, and most importantly, the DoS attacks. Finally, performance evaluation shows that our scheme is efficient for both UEs and base stations with rational computational costs.